Blue phosphorene reactivity on the Au(111) surface. (22nd September 2020) - Zhang, Wei; Enriquez, Hanna; Zhang, Xuan; Mayne, Andrew J; Bendounan, Azzedine; Dappe, Yannick J; Kara, Abdelkader; Dujardin, Gérald; Oughaddou, Hamid
Abstract: The synthesis of blue phosphorene by molecular beam epitaxy (MBE) has recently come under the spotlight due to its potential applications in electronic and optoelectronic devices. However, this synthesis remains a significant challenge. The surface reactivity between the P atoms and the Au atoms should be considered for the P/Au(111) system. In the MBE process, the temperature of the substrate is a key parameter for the growth of blue phosphorene. During the initial growth stage, irregularly shaped Phosphorus clusters grow on top of Au(111) surface at room temperature. When the substrate temperature is increased, these clusters transform into a phosphorene-like structure with a honeycomb lattice. An atom exchange reaction is observed between the P and first layer Au atoms under thermal activation at higher temperature, where the P atoms replace Au atoms to form a blue phosphorene structure within the top Au layer and at the step edges.